The impact of gastroesophageal reflux disease on the quality of life of children and adolescents in the Republic of Tyva - T. V. Polivanova; E. V. Kasparov; V. A. Vshivkov (Сибирский научный медицинский журнал, 2024)
Aim of the study was to investigate quality of life indicators in children and adolescents with gastroesophageal reflux disease (GERD) in the Mongoloid and Caucasian populations of the Republic of Tyva. Material and Methods. Schoolchildren aged 7–18 years of the indigenous (25 Mongoloids – Tuvans with GERD and 354 practically healthy) and newcomers population Republic of Tyva (5 Caucasians with GERD and 158 practically healthy) were examined using a cross-sectional method. Gastroenterological complaints and demographic information were recorded. To assess the quality of life of children, adapted Russian parent (CHQ-PF28) and child (CHQ-PF45) versions of the Child Health Questionnaire (CHQ) were used. The questionnaire allows you to assess various areas of a child’s life. Results and discussion. A decrease in the quality of life was established in schoolchildren of both ethnic populations in the presence of GERD on a number of scales as assessed by the children themselves and their parents. However, unlike parents, children’s assessments tended to decrease in the “family cohesion” section (p = 0.068), which, to a certain extent, may reflect the presence of intrafamily problems that can have a traumatic effect on the child. According to parents’ assessments, in schoolchildren with GERD in the Caucasian population, the decrease in indicators concerned only the “physical activity” scale (p = 0.039). In the Tuvan population, more extensive deviations were noted ‒ in sections “general health assessment” (p = 0.041), “physical activity” (p = 0.024), “changes in health status” (p = 0.006), “pain/ discomfort” (p = 0.037). According to the assessment of children, Caucasians with GERD did not show a decrease in indicators, and Tuvans with GERD had fewer deviations on the scales than, according to their parents. Conclusions. Tyva schoolchildren with GERD showed a decrease in quality of life indicators, which was more pronounced among Mongoloids - Tuvans, and there were differences in its assessment by the children themselves and their parents.